2010
DOI: 10.1254/jphs.09276fp
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diesel Exhaust Particles on House Dust Mite–Induced Airway Eosinophilic Inflammation and Remodeling in Mice

Abstract: Abstract. Recent research has focused on the effects of ambient particulate pollution and much evidence has indicated that particulate pollution is associated with the onset of asthma and allergy; however, the effect of diesel exhaust particles (DEP) on the development of allergen-induced airway remodeling has not been fully investigated in vivo. In the present study, we examined the effects of DEP on Dermatophagoides farinae allergens (Der f)-induced asthma-like phenotypes in mice. Mice were administered i.t.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
(31 reference statements)
2
31
2
Order By: Relevance
“…DEP exposure decreases lung function and increases neutrophil biomarkers (McCreanor et al 2007). Exposure of young and adult mice to a combination of DEP and HDM has been shown to provoke an exaggerated Th2 and mixed Th2/Th17 cell mediated inflammatory response in the airways (Takahashi et al 2009;Acciani et al 2013). Strikingly, collagen content is increased in the lungs of DEP/HDM exposed adult mice, indicative of lung remodeling.…”
Section: Th17 Instructive Signals For DC Activation In Asthmamentioning
confidence: 99%
“…DEP exposure decreases lung function and increases neutrophil biomarkers (McCreanor et al 2007). Exposure of young and adult mice to a combination of DEP and HDM has been shown to provoke an exaggerated Th2 and mixed Th2/Th17 cell mediated inflammatory response in the airways (Takahashi et al 2009;Acciani et al 2013). Strikingly, collagen content is increased in the lungs of DEP/HDM exposed adult mice, indicative of lung remodeling.…”
Section: Th17 Instructive Signals For DC Activation In Asthmamentioning
confidence: 99%
“…In an experimental asthma model using Dermatophagoides farinae allergens (Der f), the injection of DEPs with Der f enhanced the production of Th2 cytokines, eosinophil infiltration, and airway remodeling (24). Although it has not yet been clarified whether DEP-induced TSLP influences the exacerbation of these allergic manifestations in vivo, Bleck et al reported that DEPs induced TSLP production in human bronchial epithelial cells (HBECs) (25,26).…”
Section: Diesel Exhaust Particlesmentioning
confidence: 99%
“…The fine particles, mostly derived from road traffic, are ultrafine size (<100 nm) and can be deposited in the nasal and peripheric airways. These fine particles induce oxidative stress and hyper-reactivity of the respiratory tract by increasing inflammation of the respiratory tract and allergic responses such as allergic rhinitis [15]. Vendors who had a long daily working time, had a higher prevalence of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…These pollutants can induce oxidative stress and hyperreactivity of the airways. As a result, they increase allergic responses and inflammation of the respiratory tract [13] [14] [15]. Air pollution from cars is therefore a major risk factor for increasing the prevalence of allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%